Fungal Zinc Homeostasis and Its Potential as an Antifungal Target: A Focus on the Human Pathogen Aspergillus fumigatus - Pengfei Zhai; Yanfei Chai; Ling Lu (Microorganisms, 2022)
Aspergillus fumigatus is an opportunistic airborne fungus that causes severe invasive aspergillosis in immunocompromised patients. Zinc is an essential micronutrient for the growth of A. fumigatus and even for all microorganisms. An increasing number of studies have reported that fungal zinc acquisition ability plays a key role in fungal survival in hosts with an extremely zinc-limited microenvironment. The ability to fight scarcity and excess of zinc are tightly related to fungal virulence and may be used as new potential targets. Because the regulation of zinc homeostasis is important, a thorough understanding of the functional genes involved in the regulatory network for zinc homeostasis is required for fungal pathogens. The current mini-review summarized potential zinc homeostasis regulators in A. fumigatus and classified these regulators according to localization and function, which were identified or predicted based on A. fumigatus or deduced from homologs in model yeasts. Future perspectives for zinc homeostasis regulators as potential antifungal targets to treat invasive aspergillosis are also discussed.